Development and optimization of curcumin transfersomes in gel formulations as an antioxidant - Mointi, Sella Septiyani; Kuncahyo, Ilham; Harmastuti, Nuraini (Science Midwifery, 2025)
Curcumin, a natural compound with potent antioxidant properties, faces challenges in pharmaceutical use due to its poor water solubility and low bioavailability. To overcome these limitations, curcumin was encapsulated in a transfersome drug delivery system and subsequently incorporated into a gel to enhance topical delivery and improve drug release efficiency. This study aimed to evaluate the influence of phospholipid, Tween 80, and cholesterol ratios on the physicochemical properties of curcumin-loaded transfersomes and to assess the antioxidant activity of the optimized transfersome gel. A Simplex Lattice Design (SLD) using Design Expert software generated 14 formulations varying in the three components. Transfersomes were produced via the thin layer hydration method and analyzed for particle size, zeta potential, and entrapment efficiency (%EE). The resulting gel was characterized for pH, viscosity, spreadability, adhesiveness, diffusion behavior using Franz cells, and antioxidant activity through the DPPH assay. Statistical analyses employed ANOVA, Wilcoxon, and T-tests. The optimized formulation containing 700 mg phospholipid, 200 mg Tween 80, and 50 mg cholesterol yielded particles of 134.627 nm, zeta potential –8.924 mV, and 93.656% EE. Antioxidant evaluation showed IC₅₀ values of 24±1.78 ppm (transfersome) and 42±2.5 ppm (gel), both indicating very strong antioxidant activity. The gel released 23.12 µg/cm² curcumin within 150 minutes.